Physiological effects of an ultra-cycle in an amateur athlete - a case report - Neumayr, G.; Gänzer, H.; Sturm, W.; Pfister, R.; Mitterbauer, G.; Hörtnagl, H. (Journal of Sports Science & Medicine, 2002)
The physiological effects of ultraendurance exercise are poorly investigated. The present case report describes the exercise intensity of ultraendurance cycling and its physiological impacts on various organ functions in an amateur cyclist performing the Ötztal Radmarathon twice en bloque in a circuit of 2 identical laps (distance 460 km; cumulative altitude difference 11000 m). In a pre-race laboratory test the athlete's performance capacity was measured as the maximal aerobic power (VO2max= 70 ml.kg-1.min-1), a maximal power output (5.7 W kg-1) and lactate threshold of 89%. The overall intensity during the ride was moderate (HRmean = 131 b.min-1; %HRmax = 0.71) and significantly declined during the course of the race. Extensive biochemical laboratory testing performed pre- and post-race excluded major exercise-induced organ disturbances. For further confirmation and better understanding of the physiological effects of ultra-cycle events future studies of larger athlete populations are required.